DETERMINAN CAPITAL BUFFER: KAJIAN EMPIRIK INDUSTRI PERBANKAN DI INDONESIA - Estika, Winda Febi; Wahyudi, Setyo Tri (Fakultas Ekonomi dan Bisnis Universitas Brawijaya, 2023)
A high capital buffer can increase stakeholder confidence in the sustainability and stability of the bank, but causes the bank to lose the opportunity to maximize profits from business operations that should be carried out using a capital buffer. On the other hand, a low capital buffer can reduce stakeholder confidence in banks, because banks are considered to have a high risk if the economy contracts in the future. The purpose of this research is to identify and analyze the effect of bank size, liquidity risk, credit risk, operational risk, and profitability on capital buffer in KBMI 3 and 4 bank categories during 2018-2022. Using panel data regression, this study finds that partially the variables SIZE, LDR, BOPO, and ROE had a negative and significant effect on the Capital Buffer. Meanwhile, NPL has no significant effect on the Capital Buffer.